Partisipasi Penganggaran dan Budget Emphasis pada Senjangan Anggaran dengan Internal Locus of Control sebagai Pemoderasi - Julia, Ni Kadek Sintya; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi, 2024)
The purpose of this study was to find out the effect of budgetary participation and budget emphasis on budgetary slack and to find out the ability of the internal locus of control in moderating the influence of independent variables on budgetary slack. This research was conducted in Denpasar City with a total sample of 102 respondents who were determined using a purposive sampling technique. Data collection was carried out using a questionnaire, while the data analysis technique used was Moderated Regression Analysis. Based on the results of the analysis, it is known that budgetary participation has a negative effect on budgetary slack, while budget emphasis has a positive effect on budgetary slack. The existence of an internal locus of control strengthen the effect of budgetary participation and weaken the effect of budget emphasis on budgetary slack. Keywords: Budget Emphasis; Internal Locus of Control; Budgeting Participation; Budgetary Slack.